Synectic-Based Personal Analogy Learning to Improve Basic School Students 'Creative Thinking Ability - Sari, Mia Zultrianti; Hermawati, Eli (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The problem in this study is about the low creative thinking skills of elementary school students which can be seen from the passive learning activities in the classroom. Besides, teachers who are more likely to focus on completing the material cause a lack of appreciation for students to develop creative thinking skills. This research was conducted based on the results of research, journals, books, and other relevant reference sources. Data collection in this study refers to the literature study method by conducting book review studies, literature, and other notes related to the topics discussed. From the literature that has been discussed, it can be concluded that Synectic has an important role in increasing creative thinking. However, in the field implementation, the use of the Synectic model itself certainly has obstacles that can affect the success of the learning process so that it will affect the desired results.